ASPECTS OF SPIRITUAL INTELLIGENCE IN ISLAMIC EDUCATION (STUDY OF Q.S. AL-IKHLAS VERSES 1-4) - Sella Mita; Rijal Sabri; Erni Suyani (Almufida : Jurnal Ilmu-Ilmu Keislaman, 2023)
The aims of this research are: 1) To find out aspects of spiritual intelligence in Islamic education; 2) To find out aspects of spiritual intelligence contained in Surah Al-Ikhlas verses 1-4; 3) To find out the implementation of aspects of spiritual intelligence contained in Surah Al-Ikhlas verses 1-4 to the concept of Islamic education.The method used in this study uses a type of library research (library research), namely activities relating to library data collection, and recording research materials.The results of this study are: Aspects of spiritual intelligence in Islamic education consist of: Religious spiritual point of view, socio-religious relational point of view, reflected on social attitudes in terms of togetherness and social welfare, Social ethics point of view. The aspects of spiritual intelligence contained in Surah Al-Ikhlas verses 1-4 are that Allah SWT is the One and Only God, the only One, without helpers, without partners, the Most Holy of numbers and compositions, because this is the nature of absolute for God. And Allah has a special nature that is not owned by other than Him. The implementation of aspects of spiritual intelligence contained in Surah Al-Ikhlas verses 1-4 on the concept of Islamic Education is Making Tawheed as the Basis of Akhidah, Instilling Tawheed by Giving an Description of the Nature and Nature of Allah SWT, Fostering Akhidah Tauhid.